Urban distances, individual resources, and migrant entrepreneurship: a configurational analysis in China - Xie, Zhimin; Li, Yiting; Xie, Lingmin (Journal of Business Economics and Management, 2025)
Given its significance for economic and social sustainability, migrant entrepreneurship (ME) has attracted increasing attention from scholars and policymakers. However, existing research provides limited insights into how various antecedents jointly affect ME. To address this gap, this study develops a theoretical model that integrates mixed embeddedness theory and entrepreneurial opportunity construction theory to explain the processes of opportunity construction and exploitation in ME. Using 130 cross-city migration cases in China – each comprising individuals from the same origin and destination cities – we examine how urban distances and individual resources jointly shape ME. The analysis identifies three pathways to high ME: the opportunity-resource endowed path, the resource bricolage path, and the opportunity-resource matching path. Although no single factor is necessary for high ME, greater geographic distance consistently promotes it. This study advances our understanding of the interplay between urban conditions, individual resources, and ME, and further enriches the mixed embeddedness theory by integrating the opportunity construction perspective.